Continent-wide analysis of how urbanization affects bird-window collision mortality in North America. (August 2017) - Hager, Stephen B.; Cosentino, Bradley J.; Aguilar-Gómez, Miguel A.; Anderson, Michelle L.; Bakermans, Marja; Boves, Than J.; Brandes, David; Butler, Michael W.; Butler, Eric M.; Cagle, Nicolette L.; Calderón-Parra, Rafael; Capparella, Angelo P.; et al.
Abstract: Characteristics of buildings and land cover surrounding buildings influence the number of bird-window collisions, yet little is known about whether bird-window collisions are associated with urbanization at large spatial scales. We initiated a continent-wide study in North America to assess how bird-window collision mortality is influenced by building characteristics, landscaping around buildings, and regional urbanization. In autumn 2014, researchers at 40 sites (N = 281 buildings) used standardized protocols to document collision mortality of birds, evaluate building characteristics, and measure local land cover and regional urbanization. Overall, 324 bird carcasses were observed (range = 0–34 per site) representing 71 species. Consistent with previous studies, we found that building size had a strong positive effect on bird-window collision mortality, but the strength of the effect on mortality depended on regional urbanization. The positive relationship between collision mortality and building size was greatest at large buildings in regions of low urbanization, locally extensive lawns, and low-density structures. Collision mortality was consistently low for small buildings, regardless of large-scale urbanization. The mechanisms shaping broad-scale variation in collision mortality during seasonal migration may be related to habitat selection at a hierarchy of scales and behavioral divergence between urban and rural bird populations. These results suggest that collision prevention measures should be prioritized at large buildings in regions of low urbanization throughout North America. Graphical abstract: Highlights: Building size and local environmental structure influence bird-window collisions. Regional urbanization may influence bird mortality resulting from window strikes. Collision mortality was greatest at large buildings in regions of low urbanization. Prioritize collision prevention in cities and towns with low urbanization.